The Empowerment Strategy for The Food Crop Farmers in Anticipating The Climate Change - Efriyani Sumastuti (Muhammadiyah University Press, 2015)
In Indonesia, the climate change and the global warming like changes in the pattern and distribution of the rainfall give impacts on agricultural production at large, especially in the food crops. These also cause droughts, floods, landslides, forest fires, rising temperatures in urban areas, and rising sea levels. The above impacts are felt by the farmers because those can lead to a decrease in production even the crop failure. This research aims to develop an empowerment strategy of the food crop farmers in anticipating the climate change in Central Java. The data used is the primary data obtained through in-depth interviews with key-person and the Focus Group Discussion (FGD). The Analysis Hierarchy Process (AHP) is conducted to determine the program priorities and strate gies. The result of research shows that anticipating the climate change should be synergistically conducted in four aspects: human resources, technology, institutional and production, by involving various groups in the society. Various groups can be grouped into academics, businessmen / private sectors, government and community of food crop farmers / society.